GIS spatial modelling in resource planning and management - Ibrahim, Yusryzal (2008)
Pressure for development has damaged the natural environment including the upland resource areas. It is envisaged that modelling and spatial analysis can enhance the efficiency of environmental assessment. Geographic Information System (GIS) is among the more effective tool for environmental assessment to aid decision making in the planning and management of the natural environment. This research attempts to integrate the Multicriteria Analysis (MCA) and the technique of Ultimate Environmental Threshold (UET) with GIS to plan and manage the upland resource areas. The main objective of the study was to determine the limits to development of the natural resource and the limits for socioeconomic activities in the District of Cameron Highlands. The analysis was undertaken in two stages. In stage one, the sensitivity levels of the natural resource was determined through spatial analysis under the MCA method. In stage two, limitations to development and socioeconomic activities was determined with the use of UET technique. A classification of permissible and non-permissible activities was obtained and the limitations to development and socioeconomic activities was spatially patterned out for the District of Cameron Highlands. A comparative analysis of the limitations to development and socioeconomic activities with existing land use and proposed land use had indicated the damaged done to the upland resource areas from development and agriculture. Hence, pressure from indiscriminate development and illegal agriculture activities has destroyed the upland resource areas. The integration of the MCA and UET can provide much needed information to aid the planning and management of upland resource areas.